How do you solve using the quadratic formula #3x^2-2x-5=0#?

1 Answer
Aug 4, 2018

Answer:

#x = 5/3# and #-1#

Explanation:

#3x^2 - 2x - 5 = 0#

The quadratic formula is #x = (-b +- sqrt(b^2 - 4ac))/(2a)#.

We know that #a = 3#, #b = -2#, and #c = -5# based on the equation, so let's plug them into the formula and solve:
#x = (-(-2) +- sqrt((-2)^2 - 4(3)(-5)))/(2(3))#

#x = (2 +- sqrt(4 + 60))/6#

#x = (2 +- sqrt(64))/6#

#x = (2 +- 8)/6#

#x = 10/6# and #-6/6#

#x = 5/3# and #-1#

Hope this helps!